ANALISIS SISTEM AKUNTANSI TERHADAP PENCATATAN PELAPORAN KEUANGAN PADADINAS TENAGA KERJA, PERINDUSTRIAN DAN TRANSMIGRASI KABUPATEN KAPUAS HULU - B2091171010, PAULUS ARDIGO PALKALSE (MAKSI UNTAN, 2020)
The results of this study indicate that the department of labor, industry and transmigration of Kapuas Hulu financial management has been able to realize financial management that includes aspects of accountability, integrated betwent stages of budgeting administration and accountability, as mandated by government regulation number 71 of 2010 concerning government accounting standards and minister of home affairs regulation number 59 of 2007 concerning guidelines for regional financial management. The financial statement produced particularly in 2017 consist of statement of responsibility, budget realization report, balance sheet, operation report, change in equity report, and notes to financial statements. In implementing the accounting system of financial reporting system for financial reporting in the Department of labor, industry and transmigration, Kapuas Hulu is in accordance with government regulation number 71 of 2010, but in the submission of reports, it is often not punctual every month before the 15. This is due to inadequate facilities and infrastructure, including humas resources that limited accounting skills, making it late to submit financial reports.Keywords : analysis, recording, repordingDAFTAR PUSTAKAÂ Baridwan, 1994.Â  Sistem Informasi Akuntansi, BPFE, YogyakartaBastian, Indra. 2006. Akuntansi Sektor Publik: Suatu Pengantar. Jakarta: Erlangga.Bastian, Indra. 2007. Sistem Akuntansi Sektor PublikÂ  Edisi 2. Jakarta: SalembaEmpat.Dinas Tenaga Kerja, Transmigrasi dan sosial. (2016-2021). (Rencana Strategis RENSTRA).Â  Kabupaten Kapuas Hulu.Dinas Tenaga Kerja, Transmigrasi dan sosial. (2017). (Laporan Keuangan). Kabupaten Kapuas Hulu.Emzir (2011), Metodolagi Penelitian Kualitatif Analisis Data. Jakarta: Raja GrafindoEndah, NovianaÂ  (2010), Analisis Pencatatan Dan Pelaporan Keuangan Pada Satuan Kerja Perangkat Daerah (SKPD) Di Pemerintahan.Â  Kota Medan (Studi Kasus Pada Dinas Tata Kota Bangunan.Hafsah dan Diana, Mahyar (2013).Â  AnalisisÂ  Pelaporan Keuangan PadaÂ Â Â  Satuan Kerja Perangkat Daerah Pemprovsu khususnya Badan Lingkungan Hidup Pemprovsu.Halim, Abdul. 2002. Accounting Principles Board. Jakarta: Salemba Empat.Halim. Abdul. 2007. Akuntansi Keuangan Daerah. Jakarta: Salemba Empat.Halim, Abdul. 2007. Pengelolaan Keuangan Daerah. Yogyakarta: UPP STIM YKPN.Halim, Abdul. 2012. Akuntansi Sektor Publik. Jakarta: Salemba Empat.Harahap, Sofyan Syafri. 2008. Teori Akuntansi. Jakarta Rajawali Pers.Ikatan Akuntansi Indonesia. 2007. Standar Akuntansi Keuangan. Jakarta: SalembaEmpat.La Midjan. dan Azhar Susanto. 2000. Sistem Informasi Akuntansi 1. Edisi Keenam: Lembaga Informsi Akuntansi.Mardiasmo. 2002. Akuntansi Sektor Publik. Yogyakarta: Andi.Mardiasmo. 2004. Otonomi & Manajemen Keuangan Daerah. Yogyakarta: Andi.Mardiasmo. 2006. Akuntansi Sektor Publik. Yogyakarta: Andi.Mulyadi. 2001. Sistem Akuntansi. Jakarta: Salemba Empat.Pajouw, Ria Valentina (2015) Analisis Pencatatan Dan Pelaporan Keuangan Pada Unit Pelaksana Teknis Dinas Di Pemerintah. ProvinsiÂ  SulawesiÂ  Utara.Rantung, Veronika (2013). Analisis Pencatatan Dan Pelaporan Keuangan Pada Satuan KerjaÂ  Perangkat Daerah (SKPD) Di Dinas Perhubungan. Kota Manado.Â Riyanti, Umi (2011), Analisis Laporan Keuangan Pemerintah Pada Dinas Bina Marga Dan Sumber Daya Air. Kabupaten Pelalawan.Â Yakub,Â  2012 â€œPengantar Sistem Informasiâ€. Yogjakarta: Graham Ilmu.